Світовий досвід забезпечення безпеки руху пішоходів при перетині залізничних колій на пішохідних переходах - Лесів, Юлія; Ковальчук, Віталій (Видавництво Львівської політехніки, 2023)
The safety of pedestrians crossing railway tracks is relevant all over the world. The article provides statistical data on pedestrian injuries at railway crossings in Ukraine, which prompts the improvement of safety measures on railway tracks for pedestrians. The ways of increasing the safety of pedestrian traffic across the railway track, which are used in world practice, are considered, in particular, active and passive measures for the safety of pedestrian traffic in the countries of Europe, America and Australia. By modernizing the existing crossings and using world experience for the design of new railway crossings, we will be able to increase the safety level of pedestrian movement across railway tracks, especially in urban areas.